Forming limit strains for non-linear strain path of AA6014 aluminium sheet deformed at room temperature - Bressan J.D.* (2017)
© 2017 Author(s).Forming limit strain curves of conventional aluminium alloy AA6014 sheets after loading with non-linear strain paths are presented and compared with D-Bressan macroscopic model of sheet metal rupture by critical shear stress criterion. AA6014 exhibits good formability at room temperature and, thus, is mainly employed in car body external parts by manufacturing at room temperature. According to Weber et al., experimental bi-linear strain paths were carried out in specimens with 1mm thickness by pre-stretching in uniaxial and biaxial directions up to 5%, 10% and 20% strain levels before performing Nakajima testing experiments to obtain the forming limit strain curves, FLCs. In addition, FLCs of AA6014 were predicted by employing D-Bressan critical shear stress criterion for bi-linear strain path and comparisons with the experimental FLCs were analyzed and discussed. In order to obtain the material coefficients of plastic anisotropy, strain and strain rate hardening behavior and calibrate the D-Bressan model, tensile tests, two different strain rate on specimens cut at 0°, 45° and 90° to the rolling direction and also bulge test were carried out at room temperature. The correlation of experimental bi-linear strain path FLCs is reasonably good with the predicted limit strains from D-Bressan model, assuming equivalent pre-strain calculated by Hill 1979 yield criterion.